Ramon Llulls’s Worldview and Influence on Teaching Arabic in Medieval Universities - Selman Dilek (İnsan & Toplum)
Ramon Llull was an intellectual from an era when the interaction between Islam and Western Christianity was experienced in almost all its aspects. Under the domination of a military doctrine through the crusades and Reconquista, Ramon had put forward the idea of peace related to missionaries. He tried to develop a system that would explain the Catholic doctrine within the framework of a new language and logic while writing about how to achieve sovereignty in Muslim lands. Ramon related the success of the missionary to knowing the language of the societies being addressed. In this context, the language and literature of Islam must be researched in order to convince Muslim scholars and administrators. For Ramon, who had added a new dimension to the criticism of Islam, another problem that had been threatening Catholicism was the Averroism in universities. Once again, the Arabic language appeared as a source language in the struggle against medieval heresy. Because this versatile intellectual supported learning the language for all fields that encounter Islam, he established a monastery for learning Arabic and attempted to have Arabic taught at Kingdom and papal authorities. Eventually, the Council of Vienne decided to start having Arabic taught at four universitiesThis research examines the sources for studies on Arabic and Islam during the Post-renaissance and colonial periods through Ramon Llull. By studying his works, the intellectual background for teaching Arabic at medieval universities is discussed.